2014
DOI: 10.1038/eye.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal muscle transposition or oblique muscle weakening for the correction of V pattern?

Abstract: Purpose To report and to analyze the efficacy of horizontal rectus muscle transposition and inferior oblique muscle weakening in terms of pattern correction for patients with V pattern. Methods The review of the medical files identified 55 patients who had esotropia (ET) or exotropia (XT) with V pattern. The primary outcome measure was the amount of V pattern collapse (D). Results Of the 55 patients (mean age 22.1±9.5 years), 27 (49.1%) were males and 28 (50.9%) were females. The type of deviations was XT in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…All of the patients with pattern strabismus had a V pattern. Although the reported whole prevalence of pattern deviations in strabismic patients is between 12.5% and 87.7%, about 20% of strabismic patients might be expected to have a pattern deviation [1315]. Our result of patterns' frequency supports these previous findings.…”
Section: Discussionsupporting
confidence: 89%
“…All of the patients with pattern strabismus had a V pattern. Although the reported whole prevalence of pattern deviations in strabismic patients is between 12.5% and 87.7%, about 20% of strabismic patients might be expected to have a pattern deviation [1315]. Our result of patterns' frequency supports these previous findings.…”
Section: Discussionsupporting
confidence: 89%
“…28 Sekeroglu et al found that half tendon width transposition of horizontal muscles significantly decreased the amount of V pattern. 29 Children with craniosynostosis often have V-pattern horizontal strabismus. 30,31 One explanation for pattern strabismus in craniosynostosis is excyclotorsion of the orbital contents, resulting in oblique pulling directions for the nominally rectus EOMs.…”
Section: Discussionmentioning
confidence: 99%
“…Ignoring these patterns may lead to under or over corrections, with subsequent disappointment for both patient and surgeon. 4 Around 12-87% of strabismus patients have an "A" or "V" pattern. 1,2,4 The mechanism of pattern strabismus is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…4 Around 12-87% of strabismus patients have an "A" or "V" pattern. 1,2,4 The mechanism of pattern strabismus is still unclear. Many theories have been put forward regarding its etiology.…”
Section: Discussionmentioning
confidence: 99%